Free-Radical Nonbranched-Chain Oxidation of Hydrogen (International Journal of Innovative Research in Computer Science & Technology, 2018)
New reaction scheme is suggested for the  initiated nonbranched-chain addition of hydrogen  atoms to the multiple bond of the molecular oxygen.  The scheme includes the addition reaction of the  hydroperoxyl free radical to the oxygen molecule to  form the hydrotetraoxyl free radical which is  relatively low-reactive and inhibits the chain process  by shortening of the kinetic chain length. This  reaction competes with chain propagation reactions  through a hydrogen atom. Based on the proposed  scheme rate equations (containing one to three  parameters to be determined directly) are deduced  using quasi-steady-state treatment. The kinetic  description with use the obtained rate equations is  applied to the γ-induced nonbranched-chain process  of the free-radical oxidation of hydrogen dissolved in  water containing different amounts of oxygen at 296  K. The ratio of rate constants of competing reactions  and the rate constant of the addition reaction to the  molecular oxygen are defined. In this process the  oxygen with the increase of its concentration begins to  act as an oxidation autoinhibitor (or an antioxidant),  and the rate of hydrogen peroxide formation as a  function of the dissolved oxygen concentration has a  maximum. From the energetic standpoint possible  nonchain pathways of the free-radical oxidation of  hydrogen and the routes of ozone decay via the  reaction with the hydroxyl free radical (including the  addition yielding the hydrotetraoxyl free radical) in  the Earth’s upper atmosphere were considered.
Keywords: competition; hydrogen; low-reactive hydrotetraoxyl free radical; thermochemical data; etraoxyl free radical, thermochemical data